On the existence of a two-phase field in the uranium oxygen system. within the composition range 2.65 O/U < 2.67 below 1273 K. - Caneiro, Alberto; Bressan, Oscar José; Garcés, J. (North Holland Publishing Co., 1983)
Fil: Caneiro, A. Comisión Nacional de Energía Atómica; Argentina